2009
DOI: 10.1007/s10551-009-0267-x
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Chinese Accounting Students’ and Auditors’ Audit-specific Ethical Reasoning

Abstract: Chinese accounting students, Chinese auditors, national culture, ethical reasoning,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…This study uses accounting students as the participants rather than auditors. Although we have provided strong arguments for the use of final-year accounting students as proxies for entrylevel auditors (Chan & Leung 2006;Farag & Elias 2012;Fleming et al 2010;Geiger & Ogilby 2000;Hughes et al 2009;Kwock et al 2016;Ying & Patel 2016), they have not been exposed to real audit practices. Hence, the participants possibly use their own perceptions to interpret the case given in the experiment.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This study uses accounting students as the participants rather than auditors. Although we have provided strong arguments for the use of final-year accounting students as proxies for entrylevel auditors (Chan & Leung 2006;Farag & Elias 2012;Fleming et al 2010;Geiger & Ogilby 2000;Hughes et al 2009;Kwock et al 2016;Ying & Patel 2016), they have not been exposed to real audit practices. Hence, the participants possibly use their own perceptions to interpret the case given in the experiment.…”
Section: Resultsmentioning
confidence: 93%
“…Consistent with prior studies (such as Chan & Leung 2006;Farag & Elias 2012;Fleming et al 2010;Geiger & Ogilby 2000;Hughes et al 2009;Kwock et al 2016;Ying & Patel 2016), this study uses final-year accounting students in both undergraduate and professional programs as proxies for entry-level auditors. Final-year students are used because they have not been influenced by, or directly exposed to, the organizational cultures of audit firms.…”
Section: Introductionmentioning
confidence: 96%
“…Although the widespread use of DIT (Christensen et al, 2016;Fleming et al, 2010), a number of researchers in the field of accounting criticized the DIT ability to accurately capture the cognitive capacity for moral thinking without no biases and that there are more productive means for understanding the ethical decision process (Flory et al,1993;Sweeny and Fisher,1998;Bay, 2002). more troubling is the tentative connection between DIT score and behavior, and the possibility that the relationship may be quadratic rather than linear, and that This test measures moral development in general and does not measure the other aspects of operational processes of ethical decision-making.…”
Section: Rest's Model and Defining Issues Test (Dit)mentioning
confidence: 99%
“…To that effect, it has been shown that culture is closely incorporated into the accountant's development, training, standard setting and application of accounting standards (Buys, Schutte, & Andrikopoulos, 2012). It is also not surprising that as China attracts numerous foreign investments and Chinese firms accelerate their escalation of global markets, studies comparing western and eastern cultures and their relation to accounting standards are on the rise (Healy & Palepu, 2000;Flemming, Chow, & Su, 2010).…”
Section: International Standards and Cultural Differencesmentioning
confidence: 99%